Metabolic Reprogramming in HIV-Associated Neurocognitive Disorders - Allen, Charles N. S.; Arjona, Sterling P.; Santerre, Maryline; De Lucia, Claudio; Koch, Walter J.; Sawaya, Bassel E. (Frontiers in Cellular Neuroscience, 2022)
A significant number of patients infected with HIV-1 suffer from HIV-associated neurocognitive disorders (HAND) such as spatial memory impairments and learning disabilities (SMI-LD). SMI-LD is also observed in patients using combination antiretroviral therapy (cART). Our lab has demonstrated that the HIV-1 protein, gp120, promotes SMI-LD by altering mitochondrial functions and energy production. We have investigated cellular processes upstream of the mitochondrial functions and discovered that gp120 causes metabolic reprogramming. Effectively, the addition of gp120 protein to neuronal cells disrupted the glycolysis pathway at the pyruvate level. Looking for the players involved, we found that gp120 promotes increased expression of polypyrimidine tract binding protein 1 (PTBP1), causing the splicing of pyruvate kinase M (PKM) into PKM1 and PKM2. We have also shown that these events lead to the accumulation of advanced glycation end products (AGEs) and prevent the cleavage of pro-brain-derived neurotrophic factor (pro-BDNF) protein into mature brain-derived neurotrophic factor (BDNF). The accumulation of proBDNF results in signaling that increases the expression of the inducible cAMP early repressor (ICER) protein which then occupies the cAMP response element (CRE)-binding sites within the BDNF promoters II and IV, thus altering normal synaptic plasticity. We reversed these events by adding Tepp-46, which stabilizes the tetrameric form of PKM2. Therefore, we concluded that gp120 reprograms cellular metabolism, causing changes linked to disrupted memory in HIV-infected patients and that preventing the disruption of the metabolism presents a potential cure against HAND progression.